Refractory massive chylothorax following robot-assisted laparoscopic splenectomy with pericardial devascularization treated with trans-jugular intrahepatic portosystemic shunt: a case report - Deng, Xiang; Xia, Jun (Frontiers in Medicine, 2024)
The development of a chylothorax after robot-assisted laparoscopic splenectomy combined with pericardial devascularization (LSPD) is rare. The robot-assisted procedure is similar to the standard LSPD, but surgeons must remain vigilant about potential chylothorax caused by recurrence of portal hypertension in patients with cirrhosis, an event that leads to variceal bleeding in the gastric fundus or a massive chylothorax caused by a thoracic duct fistula. We report a rare case of massive chylothorax after robot-assisted LSPD and review the literature to help elucidate the mechanisms of portal hypertension after LSPD, reduce surgical complications, and improve long-term patient outcomes. After LSPD, portal pressure monitoring, coagulation function testing, and portal vein CT imaging help in excluding portal vein thromboses and ensuring appropriate anticoagulation to reduce the development of thoracic duct fistulas. If portal hypertension recurs after surgery and a highoutput chylothorax develops, conservative treatment becomes ineffective. Treatment with an active trans-jugular intrahepatic portosystemic shunt (TIPS) is recommended to lower the portal pressure.